Fibrillatory conduction in a simulated two-dimensional model of human atrial tissue: effect of the interaction of two ectopic foci. (July 2019) - Tobón, Catalina; Saiz, Javier
Atrial fibrillation (AF) is the most common tachyarrhythmia. It has been demonstrated that extra-stimuli could act as triggers for AF. In many patients it is possible that multiple ectopic foci co-exist, and their interactions may generate complex conduction patterns. Our goal is to investigate the influence of the focus frequency, conduction velocity, and anisotropy on fibrillatory pattern generation during the interaction of multiple ectopic activities under electrical remodeling conditions. Our results support the broadly accepted theory that ectopic activity acting in remodeled tissue is an initiator of reentrant mechanisms. These reentrant circuits can generate fibrillatory activity when interacting with other rapid ectopic foci and under the following conditions: high ectopic focus frequency, slow conduction velocity, and anisotropic tissue. Analyses of electrogram polymorphism allow determination of which zones of tissue permit one to know in which zone of tissue unstable activity exists. Our results give useful insights into the electrophysiological parameters that determine the initiation and maintenance of fibrillatory conduction by two ectopic foci interaction in a simulated two-dimensional sheet of human atrial cells, under chronic AF conditions.